Academic stress in school students in Peruvian rural areas during the COVID-19 pandemic: stressors, symptoms, and coping strategies - Zea Bastidas, María Nila (2024)
The Covid 19 Pandemic changed the way teaching-learning is carried out, generating problematic effects on school students, especially in rural areas where education is characterized by precariousness and limited access to basic services necessary for compliance. of basic education. One of the problematic effects could be the presence of stress, so this work aimed to investigate the degree of academic stress, stressors, stress symptoms and coping strategies in students attending school in rural Peru. Valid and reliable surveys were applied to a population of 114 school students distributed into three groups according to age and gender. It was found that 32.5% and 33.3% of students presented a moderate and severe level of academic stress respectively, there are no statistical differences due to the variation in the age of the students, but there were differences by gender, with the female being the highest frequency of a moderate and severe level of stress. Finally, the frequency of stressors (40.7%) and symptoms (42.8%) of academic stress was higher for females; However, male students presented a higher frequency of coping strategies (39.7%).